Estimate Kernel Ridge Regression Function in Multiple Regression - محمد لقاء علي; كاظم صابرين حسين (Journal of Economics and Administrative Sciences, 2018)
In general, researchers and statisticians in particular have been usually used non-parametric regression models when the parametric methods failed to fulfillment their aim to analyze the models precisely. In this case the parametic methods are useless so they turn to non-parametric methods for its easiness in programming. Non-parametric methods can also used to assume the parametric regression model for subsequent use. Moreover, as an advantage of using non-parametric methods is to solve the problem of Multi-Colinearity between explanatory variables combined with nonlinear data. This problem can be solved by using kernel ridge regression which depend on what so-called bandwidth estimation (smoothing parameters). Therefore, for this purpose two different methods were used to estimate the smoothing parameter (Maximum Likelihood Cross-Validation (MLCV) and Akaike Information Criterion (AIC)). Furthermore, a comparision between the previouse methods had been provided using simulation technique , and the method of Akaike Information Criterion (AIC) has been found to be the best for the Gaussian function .